SOLUTIONS IN HANDLING STUDENT STRESS DURING HOMELEARNING USING GAMES LEARNING METHOD - DEDY PANGGABEAN (Universitas Muhammadiyah Kalimantan Timur, 2021)
andemic times make students feel stressed during home learning. They admit that they are stressed and confused to do various activities that support their productivity. The pressure they experience during this home based learning results in their passivity when learning. This is the background of this research. The data collected proved that students experienced stress during home learning process. The results found that 90.67% of students were bored, 81.67% of students were not productive and often complained. This study aims to find the best solution in dealing with student stress during the home learning period. The research finally found that the games method was very suitable for the students' current conditions, because 89.33% of students are very happy with this method. This research uses questionnaire sheets, observation sheets, and interview sheets in the data collection process. The data that has been collected is processed using descriptive statistical data collection techniques. This research was conducted at the Lentera Harapan Tomohon School, North Sulawesi. This research was conducted for two weeks from November 02, 2020 – November 13, 2020. The subjects of this study were 90 grade VIII students. This research finally succeeded in finding a method that was suitable for the current situation. Keywords: Stressed, Home Learning, Games